ANALISIS DAN EVALUASI DRAINASE KAWASAN PERUMAHAN BLANG BEURANDANG KABUPATEN ACEH BARAT - Cut Suciatina Silvia; Dian Febtianti (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
Many of the current drainage conditions have decreased in service functions. Some problems with  decreasing  drainage  function  are  inadequate  channel  capacity,  where  the  channel  is unable to accommodate flood discharge when rainfall with high intensity.. One of the area that have problems from the drainage system is housing in Blang Beurandang I, West Aceh. With this condition, the purpose of this research is to identify the existing capacity conditions of existing channels, so that the real condition of the existing channel will be obtained. The results of the comparison between the flood discharge and the existing channel capacity obtained that there are 26 channel that are not able to accommodate the flood discharge plan that is channels43, 41, 20, 13, 14, 10, 25.11, 49.50, 26, 27, 52, 31, 5, 30, 53, 54, 2, 32, 36, 38, 40, 35, 39 and channel 42. This condition requires alternative handling so that the channel can accommodate the rain discharge with in enlarge the channel dimension. Channel planning consists of several sizes and dimensions with a budget of costs that is Rp. 736.218/000,-. The results of this study will also be a reference for the Village Government in planning the construction of drainage channels and the provide a budget as an effort to handle inundation and floods.